03 The use of scratchcards for allocation concealment and treatment allocation in a prehospital randomised controlled trial. Issue 1 (14th January 2019) - Bulger, Jenna; Rees, Nigel; Snooks, Helen; Fegan, Greg; Ford, Simon; Evans, Bridie; Longo, Mirella
Abstract : Background: RAPID (Rapid Analgesia for Prehospital Hip Disruption) study was a small study to determine the feasibility of undertaking a randomised controlled trial to test the clinical and cost-effectiveness of paramedics administering Fascia Iliaca Compartment Block (FICB) as early pain relief to patients who have fractured a hip at the scene of their injury. Objectives: To devise a simple and effective method of random allocation concealment suitable for use by Paramedics whilst in the mobile emergency prehospital setting. Methods: Traditional Methods of randomly allocating patients were considered, however none were suitable for paramedics to use during their shift. Scratchcards have been used successfully in other studies, though not prehospitally to our knowledge. Scratchcards were produced using scratch-off silver stickers which concealed the trial arm allocation. Paramedics were each allocated a unique range of consecutive numbers, used as both the scratchcard number and patient's study ID. The cards were designed to allow the paramedic to write on the incident number, date and signature. A small envelope holding the cards was prepared for each paramedic. Results: Nineteen trial paramedics used 71 scratchcards throughout the study and reported no problems randomly allocating patients using the scratchcards. Five protocol deviations reported in relation to scratchcard use. On auditing the scratchcards, all unused cards were located and no evidence of tampering with the silver panel was found. Conclusion: Paramedics can use scratchcards as a method of randomly allocating patients in trials in prehospital care. In future a method that allows only the top card to be selected should be sought. Also a more protective method of storing the cards should be used. Scratchcards can be considered for wider use in randomised controlled trials in the emergency prehospital setting.